Normal Hb A2 β-Thalassemia Trait: Frameshift Mutation (HBB: c.187_251dup) in Cis with the Hb A2' δ-Globin Gene Missense Mutation (HBD: c.49G>C). (April 2013) - Waye, John S.; Eng, Barry; Hellens, Laurie; Hohenadel, Betty-Ann; Nakamura, Lisa M.; Walker, Lynda
<x xml:space="preserve">Abstract</x> We report the case of a father and daughter who are heterozygous for a duplication of 65 bp within exon 2 of the β-globin gene, resulting in an altered and truncated β-globin chain that is predicted to be non functional. The β-globin gene mutation is in cis with the common Hb A2 ′ missense mutation of the δ-globin gene (HBD: c.49G>C), resulting in β-thalassemia (β-thal) trait with normal levels of Hb A2. This is the second report of this β0-thal mutation, and both families were associated with the Hb A2 ′ variant and normal levels of Hb A2. Laboratories should be aware of the rare occurrence of β-thal trait with normal levels of Hb A2.